Diabetes and technology in 2030: a utopian or dystopian future?. Issue 4 (9th February 2018) - Kerr, D.; Axelrod, C.; Hoppe, C.; Klonoff, D. C.
Abstract: The ability of an individual living with diabetes to have human‐to‐human contact with their healthcare provider is not keeping pace with the number of people developing diabetes. From a futurist perspective, however, this dichotomy of diabetes care represents an opportunity for digital healthcare. The focus of technological innovation is unlikely to be the replacement of the multidisciplinary diabetes team but rather the provision of meaningful individual and family support between clinic visits and, on a larger scale, the facilitation of population health management for diabetes. We can also expect to see new therapies, including implantable drug delivery systems, automated closed‐loop systems and miniaturized non‐invasive glucose monitoring systems. New digital health technologies will create a 'digital diabetes ecosystem' to enhance rather than devolve care from humans. Concerns related to data privacy and ownership will inevitably rise, thus a future for diabetes care relying heavily on technology is not inevitably utopian. Nevertheless, revolutions in the development of novel sensors, accumulation of 'big data', and use of artificial intelligence will provide exciting opportunities for preventing, monitoring and treating diabetes in the near future.